The Behavior of Traders in Islamic Business Ethics Towards Walisongo Religious Tourism in Indonesia - Abdullah, Junaidi (Universitas Islam Negeri Sunan Kudus, 2025)
One of the teachings of Islam in buying and selling or trading is Islamic business ethics. Simply put, ethics in business is defined as the study of what is good or bad, right or wrong in conducting business activities. Islamic business ethics refers to the guidelines or morals in conducting business activities in accordance with Islamic values, so that these business activities are good and right. Around the Walisongo cemetery complex, there are many vendors selling their goods, including food and beverages, with the majority selling souvenirs specific to this religious tourist site. The research method used in this study employs field research with a qualitative approach. Data collection is conducted through observation, documentation, and interviews. Data analysis involves data reduction, data display, and subsequent data verification. The findings of this study conclude that the behavior of religious tourism vendors at Walisongo has not yet implemented Islamic business ethics in practice. Many vendors have violated Islamic business ethics, such as lying or being dishonest, making false oaths, acting fraudulently, imposing their will, and prioritizing business over performing religious duties. This is attributed to low educational levels and a lack of information regarding the teachings of ethical conduct in business.